Military obedience and the law / Rahman Dato Baginda - Dato Baginda, Rahman (Faculty of Law, 1982)
The paper in the opening chapter discusses the reasons for the requirement of a separate system of military justice; the importance of discipline and obedience to orders in the Armed Forces. The standard of discipline in the Armed Florce deterwine its efficiency. Claim to justice must yield before claim of military efficiency. Obedience to orders is the cardinal principle of military organisation. Disobedience is at one's ovm risk unless one is sure that the person issuing the order is unn.uthorised to e;ive or the order goes beyond the bound of mili-tar;y service purpose. The geuidelines as to what is lawful or unlawful order is inadequately provided in the Armed Forces Act 1972.